2016
DOI: 10.1038/ncomms11545
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that phytochrome functions as a protein kinase in plant light signalling

Abstract: It has been suggested that plant phytochromes are autophosphorylating serine/threonine kinases. However, the biochemical properties and functional roles of putative phytochrome kinase activity in plant light signalling are largely unknown. Here, we describe the biochemical and functional characterization of Avena sativa phytochrome A (AsphyA) as a potential protein kinase. We provide evidence that phytochrome-interacting factors (PIFs) are phosphorylated by phytochromes in vitro. Domain mapping of AsphyA shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 48 publications
9
102
1
2
Order By: Relevance
“…However, direct in vivo evidence showing phytochrome function as a kinase was lacking until recently. Interestingly, a recent study showed that both oat (Avena sativa) and Arabidopsis phytochromes function as Ser/Thr kinases for PIFs in vitro (Shin et al, 2016). These authors have mapped the kinase domain within the PAS-GAF-PHY domains located at the N terminus of phytochromes and identified critical residues that are necessary for ATP binding.…”
Section: Kinases That Phosphorylate Pifsmentioning
confidence: 99%
“…However, direct in vivo evidence showing phytochrome function as a kinase was lacking until recently. Interestingly, a recent study showed that both oat (Avena sativa) and Arabidopsis phytochromes function as Ser/Thr kinases for PIFs in vitro (Shin et al, 2016). These authors have mapped the kinase domain within the PAS-GAF-PHY domains located at the N terminus of phytochromes and identified critical residues that are necessary for ATP binding.…”
Section: Kinases That Phosphorylate Pifsmentioning
confidence: 99%
“…PKS1 was identified originally as a kinase substrate for phytochrome A (phyA; Fankhauser et al, 1999). Whether phyA is bona fide protein kinase is still debated, although recent work has offered renewed support for its role as a protein kinase in regulating photomorphogenesis (Shin et al, 2016). While PKS proteins are required for phytochrome signaling (Lariguet et al, 2003;Schepens et al, 2008), some of the phenotypes associated with pks mutants resemble those of nph3, rpt2, and phot-deficient mutants.…”
Section: Phytochrome Kinase Substrate Proteinsmentioning
confidence: 99%
“…Full-length phytochrome cDNAs of wild-type AsphyA and the AsYVA mutant fused with a 10-amino acid streptavidin affinity-tag at the C terminus were cloned into pPIC3.5K (Invitrogen), and recombinant phytochrome proteins were prepared using the Pichia protein expression system (Invitrogen) and streptavidin affinity chromatography (IBA), as described previously (Kim et al, 2004;Shin et al, 2014Shin et al, , 2016. The QuickChange Site-Directed Mutagenesis System (Stratagene) was used to generate AsYVA with the mutagenic primers shown in Supplemental Table S1.…”
Section: Spectroscopic Analysis Of Recombinant Phytochrome Proteinsmentioning
confidence: 99%
“…Among PIFs, PIF3 is the founding member that interacts with phytochromes in a Pfr-specific manner and negatively regulates phytochrome signaling (Ni et al, 1998;Kim et al, 2003). Moreover, the physical interaction of phytochromes with PIF3 is known to lead to the latter's phosphorylation and subsequent degradation via the 26S proteasome (AlSady et al, 2006;Ni et al, 2014;Shin et al, 2016), which eventually regulates the transcription of various photoresponsive genes for photomorphogenesis in plants (Bae and Choi, 2008;Chen and Chory, 2011;Xu et al, 2015).…”
mentioning
confidence: 99%